Analisis Kekuatan Lifting Lug pada Proses Dismantling Chimney Berbasis Finite Element Analysis - Hilmansyah, Wisnu; Puspitasari, Dewi; Davareza, Tinton (Universitas Negeri Surabaya, 2025)
The dismantling process of industrial chimneys requires a safe and reliable lifting system, in which the lifting lug serves as a critical component for transferring loads to the lifting equipment. Improper lifting lug design may lead to significant safety risks during the lifting of segmented structures. This study aimed to evaluate the structural strength of a lifting lug design used in a staged chimney dismantling process using Finite Element Analysis (FEA). The chimney was divided into three loading conditions representing different segment masses, namely segments 1–5, 6–14, and 15–23. The analysis was conducted using SolidWorks Simulation with ASTM A36 structural steel and static loading assumptions. The evaluated output parameters included Von Mises stress, Von Mises strain, and total deformation. The simulation results indicated maximum Von Mises stresses of 76.85 MPa, 101.8 MPa, and 81.62 MPa for each segment group, all of which were below the material yield strength of 250 MPa. The maximum Von Mises strain remained within the elastic range, with the highest value of 77.97 MPa. The total deformation was relatively small, with maximum displacement values below 0.6 mm for all loading cases. These results demonstrate that the analyzed lifting lug design is structurally safe and suitable for application in staged chimney dismantling operations.